Firm-level consequences of export demand shocks: Swedish and Finnish exporters - Zouheir El-Sahli; Terhi Maczulskij; Katariina Nilsson-Hakkala (The Research Institute of the Finnish Economy (ETLA), 2023)
This paper analyzes how firms with different financial strength levels respond to demand shocks in their export markets. We utilize unique administrative datasets of Swedish and Finnish firms matched with national customs data from 1999 to 2014, which allows us to analyze the effects of several macroeconomic shocks affecting the export product demand and performance of exporting firms. We find that financially stronger export firms are better positioned during both positive and negative demand shocks-suffering less from the negative shocks, benefiting more from the positive shocks. While our results suggest that Swedish and Finnish firms tend to respond similarly to different export demand shocks, there are some salient differences in their survival strategies. While the financially stronger Swedish firms expanded their product lines and market areas, the Finnish firms did not make such adjustments during the 2007-2014 period of negative export demand shocks. By analyzing the firm-level survival strategies on export markets, we provide new insights into the divergent export growth trends of the two countries.
Keywords: F14; F61; L11; L25; D22; 330; Export competition; Financial strength; Firm-level; Trade flows